BANTINGAN MOROTE SIO-NAGE DITINJAU DARI POSTUR TUBUH - Bayu Nugraha Murdiansyah (BULLET : Jurnal Multidisiplin Ilmu, 2022)
In ju-jitsu martial arts, there are techniques for slamming, hitting, kicking and locking and these various techniques are widely used in matches starting from these various techniques, the researcher wants to see the slamming technique, namely how the right leg position is to do a slamming moote seo- nage in terms of posture, research "Accuracy of Foot Positioning of Ju-Jitsu Martial Athletes When Doing Morote Sion-nage Slams Judging from body posture" As a sample in this study were the 15th senior men's Ju-jitsu martial art at Unesa Open 15th year 2021 totaling 30 people. In the data collection method, interviews and direct observation were used using camcorders to take pictures during the competition with a total of 30 senior male athletes. The conclusion in this study is that the morote sio-noge slam, in terms of body posture, is for the respondent's body posture that is taller and heavier, then the appropriate slam is A slam (the position of both feet enters between the opponent's legs with the two positions knees touch the mat). For the respondent's posture which is taller and lighter body mass, the appropriate throw is type B throw (the position of the two legs is slightly in between the two opponent's legs with both knees bent). And for the same body posture as the respondent's opponent, the appropriate type of slam is type C slam (Position of both feet entering between the opponent's two legs with both knees touching the mat). Throws that are widely used during competition by athletes are type A throws (cross leg position in front of the opponent's feet) with 4 throws from different classes.